Performan Itik Lokal Jantan dengan Penggunaan Tepung Daun Beluntas (Pluchea indica L) dalam Ransum - Dwi Wijayanti; Ilyad Kumbok (Jambura Journal of Animal Science, 2021)
The research objective was to determine the use of beluntas leaf flour in rations on the performance of male local ducks. The research was conducted in the Tondo, subdistrict Mantikulore, for 6 weeks, using 80 DOD local male. The study was design using CRD with 4 treatmens and 5 replication. The treatment given was percentage of beluntas leaf flour in the ration, namely P0: ration without the addition of beluntas leaf flour, P1: 2% beluntas leaf flour, P2: 2,5% beluntas leaf flour, P3: 3% beluntas leaf flour. The analysis was used analysis of variance. The results showedthat treatments had a significant effect on ration consumption, had avery significant effect on body weight gain, ration konvertion and  income over feed costof male local ducks. The use of beluntas leaf flour up to level of 3%in the ration give the best results on growth performance, ration convertion and Income Over Feed Costof male local ducks.